Frailty Syndrome and sarcopenia in older adults with and without type 2 diabetes mellitus in the municipality of Sinop, Mato Grosso: an epidemiological study (Revista Latino-Americana de Enfermagem, 2023)
Objective: to relate Frailty Syndrome and sarcopenia in older adults with and without type 2 diabetes mellitus and identify potential risk factors for frailty and sarcopenia. Method: this descriptive epidemiological study was conducted with 140 older adults in the municipality of Sinop, Mato Grosso, Brazil. The frailty phenotype was used for the assessment of Frailty Syndrome, and a physical assessment questionnaire with calf circumference measurement was used for the assessment of sarcopenia. Results: regarding Frailty Syndrome, a higher percentage was observed in older adults with type 2 diabetes mellitus compared to those without the disease (p = 0.00). Concerning the presence of sarcopenia, older adults with and without type 2 diabetes mellitus showed similar values, with no statistical significance (p = .74). Frailty Syndrome was associated with physical inactivity (95%CI: 3.29-56.55), age over 75 years (95%CI: 3.30- 27.82), low family income (95%CI: 1.80-50.98), and comorbidities (95%CI: 4.90-5.40). However, sarcopenia was associated with the presence of physical inactivity (95%CI: 1.26-10.44), low weight/ eutrophic (95%CI: 3.32-26.76), and malnutrition/nutritional risk (95%CI: 1.30-7.70) for older adults with and without type 2 diabetes mellitus. Conclusion: older adults with diabetes have a higher vulnerability to develop Frailty Syndrome, necessitating the adoption of preventive measures in primary healthcare.